PENERAPAN DATA MINING PADA TRANSAKSI PENJUALAN PULSA MENGGUNAKAN METODE ALGORITMA APRIORI - Yoga Gemilang Kurniawan; Hardika Khusnuliawati; Firdhaus Hari Syahputra (JIMSTEK: Jurnal Ilmiah Sains dan Teknologi, 2021)
Gemilang Cell is a store that is engaged in Credit and Quota and has sales transaction data in it, one of which is the Gemilang Cell shop owner who wants to know the Pattern of Product Combination 1 with another to increase revenue in the shop. The problems faced by the current Gemilang Cell owner are the owner. confused in processing data and unable to know the pattern of product combination with one another means knowing the buyer bought the second product after buying the first product, therefore the data is processed using data mining techniques, one of the methods is the association method with a priori algorithm, data collection techniques used in this research is the observation of this research using the existing association method in the data. The results of this study were carried out using Weka software with a minimum support value of 0.10 (10%) and a confidence value of 1 (100%) rules obtained from the support and confidence values, namely 10 association rules. The association's rules result in the highest confidence value of 100% when purchasing Indosat Pulse 25 thousand, Simpati Credit 50 thousand, Indosat Sms Credit 5 thousand then buying simultaneously. Testing the system of weka in data mining with association rules can find itemset combination patterns from the sales of Pulse and Quota products at Gemilang Cell, so that information is obtained that is useful in increasing sales and can process stock inventory of Pulse and Quota products properly